Modeling the Adaptations of Agricultural Production to Climate Change (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on quantitatively assessing the impact of climate change on agricultural production based on multi-source model simulation and reveals the role and mechanism of improved management measures in adapting to climate change. Modeling is a key tool for exploring the impacts of climate change on agriculture and proposing adaptation strategies. The insights derived from this reprint will be helpful for relevant decision makers in the areas of agricultural adaptation and food security.